Government Spending in Indonesia 2005-2013 from Islamic Economic Perspective - Andriansyah, Yuli; Anto, M. Bekti Hendrie (International Journal of Economics and Financial Issues, 2016)
This research is aimed to analyse government spending in Indonesia based on its types and functions according to Islamic economic perspective. Data used in this research are government spending classified based on type and function which were secondary one collected from financial note of government and national budget and spending or Anggaran Pendapatan dan Belanja Negara in Bahasa of Republic of Indonesia, 2005-2013. Theoretical framework used in this research includes modern approach to government spending from Islamic perspective which rely only to realistic issue for current practices. The results suggest that government spending in Indonesia generally has been in line with spending proposed by Islamic economic perspectives. Government spending in Indonesia has been aimed to meet the functions suggested by Islamic teachings originally mentioned in Holy Koran or Hadith as well as derived from the two sources by contemporary ijtihad or based on what people in Indonesia ask to the government according to political and democratic mechanism adopted. However, government spending in Indonesia needs always improvement and control to ensure its capacity in achieving national purposes especially in terms of social welfare and education. Keywords: Government Spending; Islamic Economics; Fiscal Policy; Local Autonomy JEL Classifications: H5; H7; P4